Refractory Genital HPV Infection and Adult-Onset Still Disease: A Case Report and Literature Review. Issue 15 (April 2016) - Yu, Xin; Zheng, Heyi
Abstract : Abstract: Adult-onset Still disease (AOSD) is a systemic autoimmune disease (AIID) that can develop after exposure to infectious agents. Genital human papillomavirus (HPV) infection has been reported to induce or exacerbate AIIDs, such as systemic lupus erythematosus (SLE). No guidelines are available for the management of genital warts in AOSD. Case report and literature review. We report a patient who was diagnosed AOSD in the setting of refractory and recurrent genital HPV infection, demonstrating a possible link between HPV infection and AOSD. In addition, we also discuss the management of genital warts in patients with AOSD. To the best of our knowledge, no previous cases of AOSD with genital HPV infection have been reported in literature. We then conclude that the patient AOSD may be triggered by primary HPV infection. Larger number of patient samples is needed to confirm whether HPV could trigger AOSD.